Pengembangan Media Pembelajaran E-learning Menggunakan Edmodo Dengan Pendekatan Saintifik Pada Materi Sistem Sirkulasi Kelas XI SMA/MA - Nabila Latu Fany; Sa’diatul Fuadiyah; Relsas Yogica; Yusni Atifah (JURNAL PENDIDIKAN ROKANIA, 2022)
development (R & D) using the 4-D model. This study aims to determine the development of e-learning learning media using Edmodo with a scientific approach to the material circulation system for class XI SMA/MA which is valid. The research subjects were two biology lecturers at Padang State University and one biology teacher at SMA Negeri 14 Padang as validators of e-learning learning media using Edmodo. The data analysis technique used is descriptive qualitative analysis and descriptive quantitative. Feasibility testing is carried out by means of product validation by experts. The instrument used to collect data is in the form of a validation questionnaire. The validity questionnaire is a measuring tool used to assess the validity of the product that has been made. The results of the validation on e-learning media using Edmodo were 87.68% with a valid category. There are 4 aspects that are assessed from e-learning media using Edmodo, namely aspects of content feasibility, linguistic aspects, presentation aspects, and Edmodo media aspects. That way, e-learning learning media using Edmodo with a scientific approach to the circulation system material for class XI SMA/MA can be used as a tool to achieve learning objectives and can be used in the learning process.development (R & D) using the 4-D model. This study aims to determine the development of e-learning learning media using Edmodo with a scientific approach to the material circulation system for class XI SMA/MA which is valid. The research subjects were two biology lecturers at Padang State University and one biology teacher at SMA Negeri 14 Padang as validators of e-learning learning media using Edmodo. The data analysis technique used is descriptive qualitative analysis and descriptive quantitative. Feasibility testing is carried out by means of product validation by experts. The instrument used to collect data is in the form of a validation questionnaire. The validity questionnaire is a measuring tool used to assess the validity of the product that has been made. The results of the validation on e-learning media using Edmodo were 87.68% with a valid category. There are 4 aspects that are assessed from e-learning media using Edmodo, namely aspects of content feasibility, linguistic aspects, presentation aspects, and Edmodo media aspects. That way, e-learning learning media using Edmodo with a scientific approach to the circulation system material for class XI SMA/MA can be used as a tool to achieve learning objectives and can be used in the learning process.